2016
DOI: 10.1590/s0004-28032016000300012
|View full text |Cite
|
Sign up to set email alerts
|

SEQUENCE SIMILARITY BETWEEN THYROID SELF-PROTEIN AND HEPATITIS C VIRUS POLYPROTEIN: possible triggering mechanism of autoimmune thyroiditis

Abstract: -Background -Exposure to viral antigens that share amino acid sequence similar with self-antigens might trigger autoimmune diseases in genetically predisposed individuals, and the molecular mimicry theory suggests that epitope mimicry between the virus and human proteins can activate autoimmune disease. Objective -The purpose of this study is to explore the possible sequence similarity between the amino acid sequences of thyroid self-protein and hepatitis C virus proteins, using databanks of proteins and immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 36 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…Previous studies have revealed many interrelationships in embryology, phylogeny and function between the thyroid and the gastrointestinal tract through the adulthood (Miller et al, 1978). The molecular mimicry mechanisms also provide a reasonable explanation for the role of intestinal flora in triggering autoimmune diseases (Benvenga and Guarneri, 2016;Sousa Mde et al, 2016;Figura et al, 2019). Changes in the composition of gut microbiota have been confirmed to be related to the development of several autoimmune diseases, including RA (Yeoh et al, 2013), SLE (Lopez et al, 2016), MS (Shamriz et al, 2016) and Behcet's disease (Consolandi et al, 2015).…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have revealed many interrelationships in embryology, phylogeny and function between the thyroid and the gastrointestinal tract through the adulthood (Miller et al, 1978). The molecular mimicry mechanisms also provide a reasonable explanation for the role of intestinal flora in triggering autoimmune diseases (Benvenga and Guarneri, 2016;Sousa Mde et al, 2016;Figura et al, 2019). Changes in the composition of gut microbiota have been confirmed to be related to the development of several autoimmune diseases, including RA (Yeoh et al, 2013), SLE (Lopez et al, 2016), MS (Shamriz et al, 2016) and Behcet's disease (Consolandi et al, 2015).…”
Section: Discussionmentioning
confidence: 96%
“…Several infectious diseases of relevance in public health have originated in Brazil. Sousa et al34 highlighted indicators related to diseases such as dengue fever, malaria, Chagas disease, leishmaniasis, tuberculosis, and hepatitis A, revealing critical situations in several regions of the country, especially in the north, northeast, and central west, and suggesting a “proper sewer” system as a protective or minimizing indicator. An analysis of the national environmental imbalance, based on data from 2000 to 2018 and carried out by the IBGE,2 revealed that ~500,000 km 2 of natural areas were lost, with the main damage occurring in the Amazon (269,801 km 2 ) and in the Cerrado (152,706 km 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…In view of its basic infrastructure problems, Brazil’s potential role in the emergence and reemergence of infectious diseases is undeniable. As described by Sousa et al34 DENV, of the genus Flavivirus , is one of the main infectious agents circulating in the country, and it shares ancestry with 52 other known species and numerous strains and variants 35. Flaviviruses have several clinical manifestations, and there is still much to investigate on pathology, epidemiology, and their relationship with biological vectors and their hosts, based on those we know best, such as DENV, ZIKV, and YFV 9.…”
Section: Discussionmentioning
confidence: 99%
“…In our point of views, this information allows us to summarize that HLA-DRs susceptible with ATASSc presents the strong binding affinity for Top1, which well explains the direct relationship between HLA/peptide specific recognition and pathogenicity of SSc disease in a similar manner with the clinically observed information. One of the autoimmunity theories mentioned that the high conservative epitopes between foreign-antigen and self-peptide might be involved in the effective autoimmune disease 3840 . Identification of foreign-antigen as well as this Top1 self-peptide sequence is necessary to avoid triggering of ATASSc from pathogenic environment, especially for those who had HLA-DR genetic risk for the SSc disease with ATA.…”
Section: Discussionmentioning
confidence: 99%